Field testing alternatives to copper for controlling avocado fruit rots - Everett, K.R.; Timudo-torrevilla, O.E.; Hill, G.N.; Dawson, T.E. (New Zealand Plant Protection, 2008)
Six fungicides (boscalid boscalid/pyraclostrobin two formulations of copper hydroxide (Kocide Opti and Champ DP) dithianon and fluazinam) and one biological product (Biostart Target) were applied to avocado fruit in an orchard in Whangarei Products were applied as sprays on 13 February 23 March 20 April 18 June 19 July 21 August 27 September and 23 October 2007 There were five replicate trees for each treatment in a completely random block design At harvest on 2 November 20 fruit per tree were placed in a box transported to Mt Albert Research Centre within 24 h and stored at 55C for 28 days Fruit were then placed at 20C and assessed for rots when ripe There were too few stemend rots for the differences between treatments to be statistically significant but four of the fungicides significantly reduced numbers of body rots compared with the unsprayed control These were fluazinam boscalid/pyraclostrobin Kocide Opti and Champ DP